REVISIT INTENTION TO YOGYAKARTA BY DOMESTIC TOURISTS DURING A PANDEMIC - Kamila, Edita Rachma; Wicaksono, Achmad; Zaki, Achmad (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
A destination image is an image that tourists have about a destination before visiting. It can have an effect on memorable tourism experience that is a positive experience for tourists who remembered dan recalled even though they have not traveled dan also have an influence on tourist satisfaction. Apart from being influenced by the image destination variable, the satisfaction variable is also affected by memorable tourism experiences. This research focuses on domestic tourists, because in 2020 there was a corona virus pandemic. This has limited access from within Indonesia to going abroad, dan vice versa. The decline in tourists also occurred in domestic tourists, which was more than 90% in April 2020. The purpose of this study was to analyze tourism in Yogyakarta during the pandemic in 2020 . This research was conducted in Yogyakarta during the pandemic in March-October. Respondents of this study were domestic tourists visiting Yogyakarta in March-October 2020th, dan especially visiting JL. Malioboro dan Beringharjo Market. This study uses a quantitative approach using a questionnaire dan the PLS method using SmartPLS3. Respondents of this study were 80 people. The results of this study indicate that there is a significant effect between destination image dan memorable tourism experience, memorable tourism experience on satisfaction, destination image on revisit intention, tourism experience on word of mouth, dan satisfaction with revisit intention dan word of mouth. However, there is a hypothesis that does not have a significant effect, namely destination image on satisfaction.